Dam breach analysis of Kibimba Dam in Uganda using HEC‑RAS and HEC‑GeoRAS - Kiwanuka, Moses; Chelangat, Cyrus; Mubialiwo, Ambrose; Lay, Francis Joel; Mugisha, Ayubu; Mbujje, Joel Webster; Mutanda, Hosea Eridadi (Environmental Systems Research, 2023)
Dam failures have severe consequences on human life and property. In the case of an earth filled Kibimba Dam located in Eastern Uganda, the occurrence of a flood equal to or larger than the probable maximum food (PMF) could result in catastrophic economic losses including loss of human life. This study utilized the USACE Hydrologic Engineering Center’s River Analysis System (HEC-RAS) and Hydrologic Engineering Center’s Geographic River Analysis System (HEC-GeoRAS) to analyze the potential dam break of Kibimba Dam, considering overtopping and piping failure scenarios. The results of the analysis revealed that the spillway of Kibimba Dam possesses sufficient capacity to safely discharge a flood resulting from a probable maximum flood peak of 400 m3/ s. Therefore, the dam is not susceptible to breach under the overtopping failure mode. However, the dam failed under the piping failure mode. To assess the downstream impact of the dam break, the breach hydrographs resulting from piping failure were examined. Consequently, the study investigated the effects of flood propagation downstream of the dam. This resulted in varying inundation depths of up to 6 m and velocities ranging from 1.2 to 10 m/s. These findings highlight the devastating consequences of Kibimba Dam’s failure, particularly affecting rice field plantations, infrastructure, and other economic activities in the downstream area. Therefore, the outcomes of this study are crucial for the development of Emergency Action Plans that incorporate dam breach and flood routing analyses specific to the affected downstream regions
Keywords: Dam breach; HEC-RAS; HEC-GeoRAS; Kibimba